Description of the Sound Intensity of Smartphones Used by Students of SMAN 1 Permata Bener Meriah - Edi Termiko; Indra Zachreini; Cut Khairunnissa (Jurnal Multidisiplin Madani, 2023)
Hearing aids/PLDs (Personal Listening Devices) such as earphones, headphones, or headsets are often used by people to listen to sound from smartphones in order to get a good sound experience. The recommended sound volume when using PLDs is no more than 60% of the maximum volume. The use of PLDs in intensities above 85 db and for a long period of time can cause non-NIHL (non occupational noise induced hearing loss). This study aims to determine the description of the sound intensity of smartphones used by students of SMAN 1 Permata bener Meriah in the academic year 2022/2023 The method used in this study is descriptive. This study uses a cross sectional approach, namely taking primary data through checking the sound intensity when using PLDs with SLM (sound level meter). From a total of 100 samples of students of SMAN 1 Permata bener Meriah in the 2022/2023 academic year, it was found that the average sound intensity heard using PLDs was 73.76 db with a minimum value of 63.1 db and a maximum of 89 db. The conclusion of this study is that students of SMAN 1 Permata bener Meriah use PLDs with sound intensity exceeding the recommended limit